2020
DOI: 10.1155/2020/6934013
|View full text |Cite
|
Sign up to set email alerts
|

Visual Impairment among Primary School Children in Gondar Town, Northwest Ethiopia

Abstract: Background. An impairment of the visual system at or shortly after birth adversely affects educational performance of children which typically occurs through vision. Limited evidence on the magnitude and causes of visual impairment is one of the reasons for the low priority given to eye care in low-income countries. Objectives. To estimate the prevalence and determine the causes of visual impairment in primary school children in Gondar town, Northwest Ethiopia. Materials and Methods. A descriptive cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
1
13
1
1
Order By: Relevance
“…In the current meta-analysis, a total of 96 101 participants were included to estimate the pooled prevalence of blindness in Ethiopia. The studies were conducted in the different parts of Ethiopia: Nationwide,7 36 Oromia Region,51 Amhara Region,16 48 49 52–60 Tigray Region,61 Southern Nation Nationalities Peoples Region (SNNPR),62–66 Gambella and Benishangul Gumuz Regions,50 Addis Ababa City Administration8 67 68 and unspecified (ie, area) school-based study 47. All of the studies were published.…”
Section: Resultsmentioning
confidence: 99%
“…In the current meta-analysis, a total of 96 101 participants were included to estimate the pooled prevalence of blindness in Ethiopia. The studies were conducted in the different parts of Ethiopia: Nationwide,7 36 Oromia Region,51 Amhara Region,16 48 49 52–60 Tigray Region,61 Southern Nation Nationalities Peoples Region (SNNPR),62–66 Gambella and Benishangul Gumuz Regions,50 Addis Ababa City Administration8 67 68 and unspecified (ie, area) school-based study 47. All of the studies were published.…”
Section: Resultsmentioning
confidence: 99%
“…The most recent study among schoolchildren ages 5–15 y in Gondar town, northwest Ethiopia, reported unilateral prevalence of vision impairment at a PVA <6/18 was 3.7%, while an earlier study from Addis Ababa reported unilateral prevalence of 1.1% at a PVA <6/18 and 5.8% at a PVA <6/12. 35 In southern Nigeria, the prevalence of vision impairment among schoolchildren ages 6–17 y at a PVA <6/12 was 7.3%. 36 The majority of vision impairment in all studies was due to UREs.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent international assessment on vision, at least 2.2 billion individuals worldwide have a vision impairment or blindness, with at least 1 billion of them having a visual impairment that could have been prevented or recognized but not handled [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can manifest as reduced visual acuity or contrast sensitivity, visual field loss, photophobia, diplopia, visual distortion, visual perceptual difficulties, or any combination of the above. Vision impairment ranges in severity from mild visual loss to total absence of light perception or blindness [ 2 – 4 ].…”
Section: Introductionmentioning
confidence: 99%